Pengaruh Variasi Spring Plat dan Massa Roller Terhadap Torsi dan FC Pada Motor 150 cc - Bagus Kencana Surya; Listiyono Listiyono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In Indonesia, there are two types of motorcycle transmissions: manual and automatic. Users prefer automatic transmissions due to convenience and fuel efficiency. Automatic transmissions, such as CVT, CVT utilizes force for smooth and continuous gear ratio changes. CVT has disadvantages because unlike manual motors that have greater torque, especially on motorbikes that are three years old or more, such as poor acceleration at low to medium revolutions and wasteful fuel. This study aims to determine how the effect of adding spring plate and roller mass variations on torque and fuel consumption. This research uses a quantitative method with an experimental approach, by testing the independent variable to determine the results of the dependent variable. The result of this research is the use of lighter rollers can increase fuel consumption but the torque is getting smaller, because the use of lighter rollers has a fast rotation response so that the crankshaft in rotating the roller housing pulley is also lighter so it does not require a lot of fuel. While the use of heavier rollers coupled with spring plates also increases torque because the displacement ratio is faster, the torsional moment will be large which causes the torque to increase.